Biopolitics, control and pandemic policing in Victoria, Australia. (31st May 2022) - Ryan, Emma; Warren, Ian; Carlton, Bree
Abstract : The state of Victoria experienced the most far-reaching of Australia's COVID-19 control strategies in 2020. While an initial lockdown resulted in a temporary abatement of reported infections, this was followed by an extensive resurgence of cases resulting in a 112-day lockdown from the end of winter through most of spring 2020. The ongoing social and economic costs of these measures are yet to be determined. However, our contribution proposes that the links between Foucauldian biopolitics and the Deleuzian society of control offer important insights into the impacts of the Victorian lockdowns on routine police work. Specifically, we argue that the evolution of pandemic policing, within a framework seeking to promote biopolitical control of Victoria's population, unduly extended police powers and perpetuated many preexisting forms of bias and social injustice, which ultimately compromised public health. In building on the work of Arrigo et al (2020), we document the theoretical relationships between biopolitics, control and the broad idea of pandemic policing. We suggest emerging forms of preemptive control are inextricably tied to a pre-crime securitisation logic that sought to curtail the spread of COVID-19 throughout both urban and regional communities in Victoria. We frame our discussion in light of the Victorian Ombudsman's inquiry into Operation Benessere, which involved a sudden, hard lockdown in nine high-rise public housing estates in North-West Melbourne. Our analysis of this inquiry highlights the controversies of emergency pandemic enforcement and their implications for police organisational accountability. This case study reveals that biopolitical notions of control strengthened formal police powers under a state of emergency that targeted the urban poor, while immunising police from conventional forms of public accountability. We argue that these forms of biopolitical control associated with pandemic policing are characterised by the same sorts of selectivity, bias, and lack of formal accountability evident in many recent Victorian policing initiatives.